Antistatic flash-steamed nonwoven fabric and preparation method thereof
By blending antistatic agent with polymer at high temperature and using flash spinning technology, the antistatic components of the antistatic non-woven fabric are uniformly wrapped on the surface of the monofilament fiber, the stability of the antistatic ability of the non-woven fabric is solved. The problem of poor performance has achieved high-performance anti-static non-woven fabrics, which are suitable for long-term wear and widening application sites.
Patent Information
- Application Number
- CN202310249633.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-15
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-03-15
AI Technical Summary
The antistatic components of existing antistatic non-woven fabrics have weak bonding power with non-woven fabrics, resulting in poor stability of antistatic ability, and later impregnation treatment may corrode the non-woven fabric, affecting its performance.
Blend antistatic agent, initiator and polymer at high temperature and melt grafting, so that the antistatic agent is bonded to the surface of the polymer through chemical bonds, and the antistatic components are uniformly wrapped in the antistatic components by flash spinning. The surface of the monofilament fiber is bonded to the fibers by hot rolling to form a high-performance antistatic non-woven fabric.
It realizes uniform and stable bonding of antistatic components, improves the antistatic durability and performance of non-woven fabrics, and retains the original characteristics such as breathability, waterproofness, and light weight, which is suitable for long-term wear and broadens the application range.
Smart Images

Figure CN116288936B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antistatic nonwoven fabrics, and in particular to an antistatic flash-evaporated nonwoven fabric and a preparation method thereof. Background Art
[0002] Non-woven fabrics are widely used in many fields such as personal protection, medical packaging, building enclosures, protective packaging, etc. because of their excellent properties such as breathability, waterproofness, light weight, and tear resistance. Protective clothing and medical packaging materials made of non-woven fabrics have become important anti-epidemic resources. However, non-woven fabrics are very prone to static electricity in a dry environment. The generation of static electricity not only affects the comfort of wearing, but also harms the human circulatory system. At the same time, static electricity can easily absorb dust and germs in the air, further causing harm to the human body. For example, in special circumstances such as operating tables, the generation of static electricity has potential hazards to medical staff and patients, which limits the application of non-woven fabrics to a certain extent. Therefore, it is necessary to give non-woven fabrics certain antistatic properties.
[0003] The patent with application number CN202210636238.8 discloses a method for preparing an antistatic non-woven fabric, wherein the non-woven fabric is immersed in a cationic surfactant solution and a graphene oxide solution in turn, and then immersed in a silver nitrate solution for reduction reaction to obtain an antistatic non-woven fabric. This method is to directly perform post-impregnation treatment on an ordinary finished non-woven fabric. On the one hand, the binding force between the antistatic component and the non-woven fabric is weak, and the antistatic component is easy to fall off, thereby making the antistatic ability of the non-woven fabric poorly stable; on the other hand, the non-woven fabric is subjected to a later impregnation treatment, and the impregnation solution may cause a certain degree of corrosion to the non-woven fabric, destroying the structure of the non-woven fabric itself, thereby affecting its performance. Therefore, if the antistatic component is directly introduced in the preparation process of the non-woven fabric, the performance of the obtained antistatic non-woven fabric is better.
[0004] In addition, the flash spinning method has a high spinning efficiency, and the obtained non-woven fabric has a unique structure and excellent performance.
[0005] In view of this, it is necessary to design an improved antistatic flash-steamed nonwoven fabric and a preparation method thereof to solve the above problems. Summary of the invention
[0006] The object of the present invention is to provide an antistatic flash nonwoven fabric and a preparation method thereof. The preparation process firstly blends an antistatic agent, an initiator and a high molecular polymer in a specific ratio, and performs melt grafting at a high temperature so that the antistatic agent is uniformly and stably bonded to the surface of the high molecular polymer through chemical bonds; then flash spinning is used to uniformly wrap the antistatic component on the surface of the monofilament fiber; finally, hot rolling treatment is performed to further bond different fibers, and the antistatic component is uniformly bonded and wrapped on the surface of the nonwoven fabric to obtain a high-performance nonwoven fabric.
[0007] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing an antistatic flash-steamed nonwoven fabric, comprising the following steps:
[0008] S1. The antistatic agent, initiator and polymer are blended in a preset ratio, melt-grafted to obtain an antistatic masterbatch;
[0009] S2. In a high temperature and high pressure reactor at 160-200°C and 2-5MPa, the antistatic masterbatch obtained in step S1 is dissolved in dichloromethane to obtain a spinning solution, and the obtained spinning solution is ejected through the spinneret holes of a connected flash spinning device to generate a mesh fiber bundle, thereby obtaining a fiber web;
[0010] S3. The fiber web obtained in step S2 is subjected to hot rolling treatment to obtain a composite flash-steamed non-woven fabric.
[0011] As a further improvement of the present invention, in step S1, the structural formula of the antistatic agent is:
[0012]
[0013]
[0014] One of them.
[0015] As a further improvement of the present invention, in step S1, the mass percentages of the initiator, the antistatic agent and the high molecular polymer are 0.5-1wt%: 2-3.5wt%: 95-97wt%.
[0016] As a further improvement of the present invention, in step S1, the temperature of melt grafting is 180-250°C.
[0017] As a further improvement of the present invention, in step S2, the mass percentages of antistatic masterbatch and dichloromethane in the spinning solution are 8-12wt%:88-92wt%.
[0018] As a further improvement of the present invention, in step S2, the air flow velocity ejected from the spinneret of the flash spinning equipment is 8000-11000 m / min, the spinning speed is 1500-2000 m / min, and the pore size of the spinneret is 0.1-5 μm.
[0019] As a further improvement of the present invention, in step S1, the initiator is one of dicumyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxy-3-yne and benzoyl peroxide.
[0020] As a further improvement of the present invention, in step S1, the high molecular polymer is one of polyethylene and polypropylene.
[0021] As a further improvement of the present invention, the pressure compensation of the high-temperature and high-pressure reactor in step S2 adopts one of high-purity nitrogen, carbon dioxide and argon.
[0022] In order to achieve the above-mentioned purpose of the invention, the present invention provides a preparation method as described above.
[0023] The beneficial effects of the present invention are:
[0024] (1) The present invention provides a method for preparing an antistatic flash nonwoven fabric, which comprises the following steps: firstly, an antistatic agent, an initiator and a high molecular polymer are blended in a specific ratio, and melt grafted at a high temperature so that the antistatic agent is uniformly and stably bonded to the surface of the high molecular polymer through chemical bonds to obtain an antistatic masterbatch; then, the antistatic masterbatch is dissolved in dichloromethane in a high temperature and high pressure reactor, and the high temperature and high pressure further strengthen the bonding between the antistatic agent and the polyolefin, so that crosslinking occurs between different antistatic agent molecular chains and between the antistatic molecular chains and the polyolefin molecular chains; then, the antistatic masterbatch is prepared by flash spinning. The masterbatch is rapidly cooled and solidified under high-speed spinning to form monofilament fibers. In this process, the cross-linked structure formed between different antistatic agent molecular chains and between the antistatic molecular chains and polyolefin molecular chains remains unchanged, and the antistatic components are evenly wrapped on the surface of the monofilament fibers; multiple monofilament fibers form a fiber web on the accumulation belt, and the antistatic agents on the surfaces of different fibers in the fiber web are further bonded through hydrogen bonds to form a fiber web with a special structure; finally, through hot rolling treatment, different fibers are further bonded, and the antistatic components are evenly bonded and wrapped on the surface of the non-woven fabric to obtain a high-performance non-woven fabric.
[0025] (2) The present invention provides a method for preparing an antistatic flash-steamed non-woven fabric, wherein the antistatic powder used has good compatibility, heat resistance, stability, and non-toxicity; a grafting method is adopted to enable the modified polymer material to maintain a long-term antistatic effect, thereby increasing the antistatic durability of the non-woven fabric; at the same time, the original properties of traditional non-woven fabrics such as air permeability, waterproofness, light weight, and tear resistance are retained, making it suitable for people to wear for a long time, thereby broadening the scope of application of non-woven fabrics in specific environments; the preparation method is simple and efficient, and a twin-screw extruder is used for melt blending and granulation, which can implement mechanized mass production, improve production efficiency, and meet industrialization needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is the grafting principle diagram of the present invention. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0028] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0029] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0030] See also Figure 1 As shown, the present invention provides a method for preparing an antistatic flash-steamed nonwoven fabric, comprising the following steps:
[0031] S1. Melt grafting
[0032] The initiator, antistatic agent and high molecular polymer are added into a twin-screw extruder according to the mass percentage of 0.5-1wt%: 2-3.5wt%: 95-97wt%, the temperature is controlled at 180-250°C for blending and granulation, and the antistatic masterbatch is obtained by melt grafting.
[0033] The initiator is one of dicumyl peroxide (DCP), 2,5-dimethyl-2,5-di-tert-butylperoxy-3-yne (BTBHY) and benzoyl peroxide (BPO).
[0034] The structural formula of the antistatic agent is:
[0035]
[0036] One of them.
[0037] The high molecular polymer is one of polyethylene and polypropylene, preferably polyethylene.
[0038] Specifically, if Figure 1 As shown in the figure, under high-temperature melting environment, the peroxide bonds in the DCP molecules are first broken to generate highly active oxygen free radicals; then the highly active oxygen free radicals grab the hydrogen atoms in the polyethylene chain to generate stable cumyl alcohol and polyethylene molecules with active free radicals; finally, the polyethylene molecules with active free radicals add to the double bonds of the antistatic agent, grafting the antistatic agent onto the polyethylene molecular chain to obtain a polyethylene masterbatch with antistatic properties.
[0039] S2. Flash Spinning
[0040] In a high-temperature and high-pressure reactor at 160-200° C. and 2-5 MPa, the antistatic masterbatch obtained in step S1 is dissolved in dichloromethane to obtain a spinning solution, wherein the mass percentage of the antistatic masterbatch and dichloromethane is 8-12wt%:88-92wt%. The discharge control valve of the high-temperature and high-pressure reactor is opened, and the air flow velocity (i.e., the spinning speed) ejected from the spinneret of the flash spinning device is controlled to be 8000-11000m / min, and the spinning speed is 1500-2000m / min so that the obtained spinning solution is ejected from the spinneret hole of the flash spinning device, and flash spinning is performed in a preset spinning zone whose temperature is higher than the boiling point of the solvent used for the spinning solution. As the solvent evaporates rapidly, the polymer is re-solidified into a sub-nanometer fineness monofilament fiber, and different monofilament fibers are entangled into a mesh fiber bundle, thereby forming a fiber web.
[0041] Among them, the aperture of the spinneret of the flash spinning equipment is 0.1-5μm. By ensuring a smaller spinneret aperture and a higher spinneret speed and spinning speed, ultrafine fibers can be obtained, making the prepared composite non-woven fabric denser and with uniform pores, so that the antistatic components are evenly and densely distributed on the surface of the non-woven fabric, and the molecular chains of different antistatic components are cross-linked with each other and bonded through hydrogen bonds, forming a special cross-linking and bonding structure on the surface of the non-woven fabric, further improving the stability of the antistatic components, and thus improving the antistatic performance of the non-woven fabric.
[0042] In this process, the spinning solution is sprayed from a high temperature and high pressure environment to the spinning area where the temperature and pressure drop suddenly. The organic solvent in the composite spinning solution evaporates rapidly, and the antistatic masterbatch is rapidly cooled and solidified under high-speed spinning to form a single fiber (and the high-speed airflow ejected from the spinneret can stretch the spinning solution to form ultra-fine fibers). The single fiber is directly deposited on the accumulation belt to form a fiber web. In addition, during the evaporation of the organic solvent, tiny pores will be formed on the single fiber, so that the obtained non-woven fabric has stable antistatic properties and air permeability, expanding its application areas.
[0043] The pressure compensation of the high temperature and high pressure reactor adopts one of high purity nitrogen, carbon dioxide and argon.
[0044] S3.Hot rolling forming
[0045] The fiber web obtained in step S2 was subjected to a thermal bonding treatment at 80-130°C to obtain a surface resistivity as low as 1.4×10 6 Ω, charge half-decay time as low as 0.2s, excellent grade antistatic flash non-woven fabric.
[0046] The present invention also provides an antistatic flash-steamed nonwoven fabric, which is prepared by the above-mentioned preparation method.
[0047] The present invention is described in detail below through specific embodiments.
[0048] Example 1
[0049] A method for preparing an antistatic flash-steamed nonwoven fabric comprises the following steps:
[0050] S1. Melt grafting
[0051] Dicumyl peroxide (DCP), antistatic agent and polyethylene were added into a twin-screw extruder in a mass percentage of 0.6wt%:3wt%:96.4wt%, and the temperature was controlled at 200°C for blending and granulation, and antistatic masterbatch was obtained by melt grafting.
[0052] The structural formula of the antistatic agent is:
[0053]
[0054] S2. Flash Spinning
[0055] In a high-temperature and high-pressure reactor at 180°C and 4MPa, the antistatic masterbatch obtained in step S1 is dissolved in dichloromethane to obtain a spinning solution, wherein the mass percentage of the antistatic masterbatch and dichloromethane is 10wt%:90wt%. The discharge control valve of the high-temperature and high-pressure reactor is opened, and the air flow velocity ejected from the spinneret is controlled to be 10000m / min, and the spinning speed is 1800m / min, so that the obtained spinning solution is sprayed from the spinneret hole of the flash spinning device to the preset spinning zone at a temperature of 40°C for flash spinning. With the rapid volatilization of the solvent, the polymer is re-solidified into a sub-nanometer fineness monofilament fiber, and different monofilament fibers are entangled into a mesh fiber bundle, thereby forming a fiber web.
[0056] Among them, the aperture of the spinneret of the flash spinning equipment is 3 μm.
[0057] S3.Hot rolling forming
[0058] The fiber web obtained in step S2 is subjected to a thermal bonding treatment at 100° C. to obtain an antistatic flash-steamed nonwoven fabric.
[0059] Example 2 and Comparative Examples 1-2
[0060] A method for preparing an antistatic flash-steamed nonwoven fabric is disclosed. Compared with Example 1, the difference lies in that, in step S1, the mass percentages of dicumyl peroxide (DCP), antistatic agent and polyethylene are different, and the rest are substantially the same as Example 1 and will not be repeated here.
[0061] The antistatic flash-steamed nonwoven fabrics prepared in Examples 1-2 and Comparative Examples 1-2 were tested for performance, and the results are shown in Table 1:
[0062] Table 1 Relevant properties of nonwoven fabrics prepared in Examples 1-2 and Comparative Examples 1-2
[0063]
[0064] As shown in Table 1, when the mass percentages of dicumyl peroxide (DCP), antistatic agent and polyethylene vary within a certain range (Examples 1 and 2), the antistatic properties of the obtained nonwoven fabric do not change much. When dicumyl peroxide (DCP) and antistatic agent are not included (Comparative Example 1), the obtained nonwoven fabric is an ordinary nonwoven fabric with a surface resistivity of up to 1.5×10 14 When the content of dicumyl peroxide (DCP) and antistatic agent is too high (Comparative Example 2), the antistatic property of the obtained nonwoven fabric is still poor. This is mainly because when the content of dicumyl peroxide (DCP) and antistatic agent is too high, on the one hand, the mixing uniformity of the three in the molten state is poor; on the other hand, the excessive content of antistatic agent molecules repel each other, thereby affecting the grafting efficiency, and then affecting the structure and performance of the nonwoven fabric.
[0065] In order to test the antistatic durability of the antistatic flash-steamed nonwoven fabric prepared in the present invention, the antistatic flash-steamed nonwoven fabric prepared in Example 1 was washed twice, and the surface resistivity was still as low as 1.8×10 10 Ω.
[0066] Embodiment 3-5
[0067] A method for preparing an antistatic flash-steamed nonwoven fabric, compared with Example 1, is different in that, in step S1, the structure of the antistatic agent is different, and the rest is substantially the same as Example 1, which will not be repeated here. The structures of the antistatic agents in Examples 3-5 are:
[0068]
[0069] The antistatic flash-steamed nonwoven fabrics prepared in Examples 3-5 were subjected to performance tests, and the results are shown in Table 2:
[0070] Table 2 Nonwoven fabric related properties prepared in Examples 3-5
[0071] Example Surface resistivity / Ω Charge half decay time / s grade Example 1 <![CDATA[1.4×10 6 ]]> 0.2 very good Example 3 <![CDATA[1.7×10 6 ]]> 0.6 very good Example 4 <![CDATA[1.5×10 6 ]]> 0.4 very good Example 5 <![CDATA[1.8×10 6 ]]> 0.7 very good
[0072] As shown in Table 2, when the carbon chain of the antistatic agent is shortened (Examples 1 and 3), the antistatic performance of the obtained nonwoven fabric is reduced, which is mainly because when the carbon chain of the antistatic agent is shorter, the antistatic agent and the polyolefin molecular chain are not fully entangled, and the structure of the obtained antistatic nonwoven fabric is deviated, thereby affecting its performance. When one hydroxyl group of the antistatic agent is replaced by an amino group (Examples 1 and 4), the performance deviation of the obtained nonwoven fabric is small. When both hydroxyls of the antistatic agent are replaced by carboxyl groups (Examples 1 and 5), the antistatic performance of the obtained nonwoven fabric is reduced, which is mainly because the steric hindrance of the carboxyl group is large, which will affect the entanglement of the antistatic agent molecules and the polyolefin molecular chains. However, by changing the molecular structure of the antistatic agent, the antistatic performance of the obtained nonwoven fabric is better overall.
[0073] Examples 6-7 and Comparative Examples 3-4
[0074] A method for preparing an antistatic flash-steamed nonwoven fabric is provided. Compared with Example 1, the difference lies in that, in step S1, the temperature of melt grafting is different. The other aspects are substantially the same as Example 1 and will not be described in detail herein.
[0075] The antistatic flash-steamed nonwoven fabrics prepared in Examples 6-7 and Comparative Examples 3-4 were tested for performance, and the results are shown in Table 3:
[0076] Table 3 Relevant properties of nonwoven fabrics prepared in Examples 6-7 and Comparative Examples 3-4
[0077]
[0078] As shown in Table 3, when the temperature of melt grafting gradually increases within a certain range (Examples 1 / 6 / 7), the surface resistance of the obtained nonwoven fabric first decreases and then slightly increases. This may be because as the melt grafting temperature increases, the compatibility of the three is better, the melting is more uniform, and the grafting is more uniform, thereby improving the antistatic performance. However, as the temperature further increases (Comparative Example 4), the antistatic performance of the obtained antistatic nonwoven fabric is significantly poor. This is mainly because when the temperature is too high, the molecular structure of the antistatic agent and the polyolefin is destroyed, the polyolefin chain is broken, and the grafting of the antistatic agent and the polyolefin is affected, thereby affecting the structure of the obtained antistatic nonwoven fabric and changing its performance.
[0079] Examples 8-9 and Comparative Examples 5-6
[0080] A method for preparing an antistatic flash-steamed nonwoven fabric is provided, compared with Example 1, except that, in step S2, the mass percentages of the antistatic masterbatch and dichloromethane are different, and the rest are substantially the same as Example 1 and will not be described herein.
[0081] The antistatic flash-steamed nonwoven fabrics prepared in Examples 8-9 and Comparative Examples 5-6 were tested for performance, and the results are shown in Table 4:
[0082] Table 4 Relevant properties of nonwoven fabrics prepared in Examples 8-9 and Comparative Examples 5-6
[0083]
[0084] As shown in Table 4, when the concentration of the spinning solution changes within a certain range (Examples 1 / 8 / 9), the performance of the obtained antistatic agent deviates, but the antistatic performance is generally good. When the concentration of the spinning solution is too low or too high (Comparative Examples 5 and 6), the antistatic performance of the nonwoven fabric is reduced; this is mainly because, when the concentration of the spinning solution is too low, the spinning stream ejected from the spinneret is easily broken, destroying the structure of the monofilament, and affecting the entanglement of the antistatic agent and the polyolefin molecular chain, affecting the antistatic performance; when the concentration of the spinning solution is too high, the uniformity of the spinning solution is poor, and the spinning stream is not easy to eject from the spinneret, and the degree of entanglement between the thicker monofilaments is poor, which affects the structure of the obtained nonwoven fabric, and then affects its performance.
[0085] Embodiment 10-11
[0086] A method for preparing an antistatic flash-steamed nonwoven fabric is provided. Compared with Example 1, the difference lies in that, in step S2, the temperature and pressure of the high-temperature reactor are different. The other aspects are substantially the same as Example 1 and will not be described in detail here.
[0087] The antistatic flash-steamed nonwoven fabrics prepared in Examples 10-11 were subjected to performance tests, and the results are shown in Table 5:
[0088] Table 5 Nonwoven fabric related properties prepared in Examples 10-11
[0089]
[0090]
[0091] It can be seen from Table 5 that with the increase of the temperature and pressure of the high-temperature and high-pressure reactor, the surface resistance of the obtained non-woven fabric first decreases and then increases, and the change trend is large, indicating that the temperature and pressure of the high-temperature reactor have a great influence on the antistatic properties of the non-woven fabric.
[0092] Examples 12-14
[0093] A method for preparing an antistatic flash non-woven fabric, compared with Example 1, is different in that, in step S2, the aperture of the spinneret and the air flow velocity of the spinning stock solution ejected from the spinneret of the flash spinning equipment are different, and the rest are roughly the same as Example 1 and will not be repeated here.
[0094] The antistatic flash-steamed nonwoven fabrics prepared in Examples 12-14 were subjected to performance tests, and the results are shown in Table 6:
[0095] Table 6 Nonwoven fabric related properties prepared in Examples 12-14
[0096]
[0097] It can be seen from Table 6 that as the diameter of the spinneret hole increases (Examples 1 / 10 / 11), the surface resistance of the obtained nonwoven fabric first decreases and then increases. This indicates that the diameter of the fiber monofilament has an impact on the performance of the nonwoven fabric.
[0098] By reducing the speed of the ejected air flow (Example 1 / 12), the surface resistivity of the obtained non-woven fabric increases. This is mainly because, when the speed of the ejected air flow is low, the tensile force between the fibers is small, the diameter of the obtained monofilament fibers becomes larger, and the entanglement between different monofilaments and between the antistatic agent and the polyolefin molecular chain is reduced, which in turn affects the performance of the non-woven fabric.
[0099] Comparative Example 7
[0100] A method for preparing an antistatic flash-steamed nonwoven fabric, compared with Example 1, is different in that in step S1, the grafting is carried out in a solution, specifically, PP is dissolved in xylene (solvent), and then an antistatic agent and DCP are added to carry out a solution grafting reaction. The rest is substantially the same as Example 1 and will not be described in detail here. The surface resistivity of the obtained antistatic flash-steamed nonwoven fabric is 1.2×10 11 Ω, the charge half-decay time is 12S, the grade is ordinary, and the antistatic performance is significantly worse than that of Example 1, indicating that the grafting efficiency in the molten state is significantly higher than that in the solution. At the same time, the entangled chain of the special structure formed by the antistatic agent and the polyolefin in the molten state is more stable, and the antistatic performance of the obtained non-woven fabric is better.
[0101] Comparative Example 8
[0102] A method for preparing an antistatic flash-steamed nonwoven fabric is different from that in Example 1, in step S1, no initiator is added, and the mixture is directly blended. The other aspects are substantially the same as those in Example 1 and will not be described in detail herein. The surface resistivity of the obtained antistatic flash-steamed nonwoven fabric is 1.5×10 11 Ω, the charge half-decay time is 13S, the grade is ordinary, and the antistatic performance is significantly worse than that of Example 1. This is mainly because when no initiator is added, there is no strong force connecting the polyethylene and the antistatic agent, and the two polymers of polyethylene and the antistatic agent cannot be mixed due to steric hindrance, resulting in poor performance of the non-woven fabric.
[0103] Comparative Example 9
[0104] A method for preparing an antistatic flash nonwoven fabric, compared with Example 1, the difference is that in step S1, the antistatic agent is a 1-phenylimidazole ionic liquid antistatic agent, the specific structure is as follows, wherein R is C 4H 9 , X is Cl, that is, the antistatic agent is 1-phenylvinyl-3-butyl imidazole chloride, and the rest is substantially the same as in Example 1, which will not be described again. The surface resistivity of the obtained antistatic flash-steamed nonwoven fabric is 1.5×10 12 Ω, the charge half-decay time is 15S, the grade is ordinary, and the antistatic performance is significantly worse than that of Example 1, which further illustrates the high efficiency of the antistatic agent used in the present invention.
[0105]
[0106] Comparative Example 10
[0107] A method for preparing an antistatic flash-steamed nonwoven fabric, compared with Example 1, is different in that in step S2, a wet spinning process is adopted, and the rest is substantially the same as Example 1 and will not be described again. The surface resistivity of the obtained antistatic flash-steamed nonwoven fabric is 1.6×10 11 Ω, the charge half-decay time is 14S, the grade is ordinary, and the antistatic performance is significantly worse than that of Example 1, indicating that the antistatic performance of the present invention is the result of the combined effect of the antistatic agent and flash spinning.
[0108] In summary, the present invention provides an antistatic flash nonwoven fabric and a preparation method thereof. In the preparation process, an antistatic agent, an initiator and a high molecular polymer are first blended in a specific ratio, and melt grafted at a high temperature so that the antistatic agent is uniformly and stably bonded to the surface of the high molecular polymer through chemical bonds; then flash spinning is used to uniformly wrap the antistatic component on the surface of the monofilament fiber; finally, hot rolling treatment is performed to further bond different fibers, and the antistatic component is uniformly bonded and wrapped on the surface of the nonwoven fabric to obtain a high-performance nonwoven fabric; the preparation method is simple and efficient, and the surface resistivity of the obtained antistatic nonwoven fabric is as low as 1.4×10 6 Ω, charge half-decay time as low as 0.2s, good grade; at the same time, the antistatic non-woven fabric is dense and has a certain air permeability, which expands its application places.
[0109] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an antistatic flash-steamed nonwoven fabric, characterized in that: The steps include: S1. The antistatic agent, initiator and polymer are blended according to a preset ratio, melt grafted, and an antistatic masterbatch is obtained; the polymer is one of polyethylene and polypropylene; the mass percentage of the initiator, antistatic agent and polymer is 0.5-1wt%: 2-3.5wt%: 95-97wt%; S2. In a high temperature and high pressure reactor at 160-200°C and 2-5MPa, the antistatic masterbatch obtained in step S1 is dissolved in dichloromethane to obtain a spinning solution, and the obtained spinning solution is ejected through the spinneret holes of a connected flash spinning device to generate a mesh fiber bundle, thereby obtaining a fiber web; in the spinning solution, the mass percentage of the antistatic masterbatch and dichloromethane is 8-12wt%:88-92wt%; S3. The fiber web obtained in step S2 is subjected to hot rolling to obtain a composite flash-steamed nonwoven fabric; In step S1, the structural formula of the antistatic agent is: 、 、 、 One of them.
2. The method for preparing the antistatic flash-steamed nonwoven fabric according to claim 1, characterized in that: In step S1, the temperature of melt grafting is 180-250°C.
3. The method for preparing the antistatic flash-steamed nonwoven fabric according to claim 1, characterized in that: In step S2, the air flow velocity ejected from the spinneret of the flash spinning equipment is 8000-11000 m / min, the spinning speed is 1500-2000 m / min, and the pore size of the spinneret is 0.1-5 μm.
4. The method for preparing the antistatic flash-steamed nonwoven fabric according to claim 1, characterized in that: In step S1, the initiator is one of dicumyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxy-3-yne and benzoyl peroxide.
5. The method for preparing the antistatic flash-steamed nonwoven fabric according to claim 1, characterized in that: The pressure compensation of the high temperature and high pressure reactor in step S2 adopts one of high purity nitrogen, carbon dioxide and argon.
6. An antistatic flash-steamed nonwoven fabric, characterized in that: The preparation method is described in any one of claims 1 to 5.
